Labor unrest in Bangladesh RMG sector: does active labour union reduce the risk of labor unrest in RMG sector? - Tamanna, Urmi (BRAC University, 2013)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2010.